Fighting chance the struggle over woman suffrage and black suffrage in Reconstruction America - Dudden, Faye E. (Oxford University Press, 2011)
The advocates of woman suffrage and black suffrage came to a bitter falling-out in the midst of Reconstruction, when Elizabeth Cady Stanton opposed the Fifteenth Amendment for granting black men the right to vote but not women. How did these two causes, so long allied, come to this? This book offers answers to this question and reveals that racism was not the only cause, but that the outcome also depended heavily on money and political manoeuvre.